Gut microbes regroup to aid defence after infection - Kendall, Melissa M. (Nature, 2021)
Resident gut microbes can help to block infection, but the mechanisms involved are not fully understood. It has now been found that changes in the microbial community after infection boost the level of a molecule that combats harmful bacteria.